Pandemic Response: Best Practices in IT Leadership - Davidson, Jason (Journal of Leadership, Accountability and Ethics, 2024)
The rapid spread of the COVID-19 virus resulted in shelter-in-place orders disrupting business operations and supply chains. IT leadership was faced with the rapid implementation of crisis management and business continuity plans as well as on-the-fly adaptations required to stay operational. Four CIOs from various businesses discussed the challenges of dealing with a rapidly spreading pandemic, strategies to mitigate the loss of business continuity, and lessons learned in the transition to hybrid or fully remote work environments. This paper recounts and analyzes the best practices gained from these interviews. Data was collected through online interviews with CIOs from for-profit and non-profit businesses. The transcripts of the recorded interviews were then analyzed for similar strategic approaches, aspects of success, and areas that needed improvement. The results revealed best practices in dealing with the loss of a centralized work environment, strategies to leverage technology